PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN FAKULTAS EKONOMI DAN BISNIS ISLAM UIN RADEN FATAH PALEMBANG - Riri Hanifa; Abu Daud (Jurnal Manajemen Bisnis Unbara, 2022)
This study tries to analyze the influence of leadership style on employee performance at the Faculty of Economics and Islamic Business UIN Raden Fatah Palembang. The data used is secondary data obtained through a questionnaire instrument. The sampling technique used saturated sampling as many as 53 employees. The analysis technique used is simple linear regression. The results of the study indicate that leadership style has a significant positive direct effect on employee performance at the Faculty of Economics and Islamic Business, UIN Raden Fatah Palembang.